Consumer acceptance and adoption of metaverse environments in South Africa - Malebana-Metsing, Sekete (University of the Witwatersrand, Johannesburg, 2023)
This research focuses on the acceptance and adoption drivers of metaverse (virtual world) environments in South Africa. In particular, it explores the influence of enabling technology, digital identity, access to economic resources in the form of virtual currencies and alternative digital payment capabilities as motivators of metaverse acceptance. The effect of an individual’s social circle is also examined in detail. The theoretical model used in this research is the Universal Theory of Acceptance and Use of Technology (UTAUT). The study used a cross-sectional, quantitative methodology that followed a positivist approach. Primary data was collected from a sample of adult individuals residing in South Africa through a self-administered online questionnaire. Data analysis included correlation analysis, item reduction, exploratory factor analysis, moderation variable analysis and multiple regression analysis for the constructs represented in UTAUT. The findings indicate that enabling technology, digital identity, social influence and access to economic resources (virtual currencies) are strong predictors of individual behavioural intention and usage behaviour regarding the metaverse technology. The current state of the metaverse technology in the country is considered nascent, although there is wider acceptance of console and personal computing gaming in virtual world games such as Second Life, Roblox Minecraft, World of Warcraft and Fortnite. This indicates that immersive virtual reality technology is yet to mature to the point where it can meet the needs of consumers.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: User acceptance drivers; Adoption; Virtual world; Digital payment strategies; Metaverse; Virtual reality; UCTD; SDG-8: Decent work and economic growth